Historiographical Basis of the Researches of the Process of Adaptation of Personality in the Works of Scientists- Psychologists (1980-s -1990-s) - Halus, Oleksandr (Pedagogical Discourse, 2013)
In the context of historiographic study of the research of the process of personality’s adaptation in the works of domestic scientists-psychologists (1980-s -1990-s) has been analyzed in the article. The attention is paid to the interpretation of the concepts «adaptation», «psychological adaptation», types of adaptation. The information on the research problems of psychological adaptation of the personality in the works of domestic scientists-psychologists of the mentioned period has been offered. Separately the concept of personalization of A.V.Petrovskyi, and the concept of the system study of the process of adaptation in connection with specific components (energetical, environmental, social, active, professional, individual and personal) of V.A.Semychenko have been analyzed.